Rapid isolation of cancer cells using microfluidic deterministic lateral displacement structure - Liu, Zongbin (American Institute of Physics, 2013)
This work reports a microfluidic device with deterministic lateral displacement (DLD) arrays allowing rapid and label-free cancer cell separation and enrichment from diluted peripheral whole blood, by exploiting the size-dependent hydrodynamic forces. Experiment data and theoretical simulation are presented to evaluate the isolation efficiency of various types of cancer cells in the microfluidic DLD structure. We also demonstrated the use of both circular and triangular post arrays for cancer cell separation in cell solution and blood samples. The device was able to achieve high cancer cell isolation efficiency and enrichment factor with our optimized design. Therefore, this platform with DLD structure shows great potential on fundamental and clinical studies of circulating tumor cells.